HUBUNGAN ANTARA DISIPLIN BELAJAR DENGAN HASIL BELAJAR PKN PADA SISWA KELAS IV SDN 255/VI SUNGAI KAPAS TAHUN AJARAN 2025/2026 - Adelia Putri Andini; Dinda Suci Amelia; Haryoka; Melsa Kartika; Resi Septia Isra; Leni Marlina; Diva Apri Mulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by low student learning discipline and Civics learning outcomes that did not meet the Learning Objective Achievement Criteria (KKTP). Of the 66 students, only 28 (42%) achieved completion. This is due to a lack of student discipline in learning. Civics learning outcomes are influenced not only by cognitive factors but also by students' mental attitudes toward learning, one of which is learning discipline. This study aims to determine the relationship between learning discipline and Civics learning outcomes in fourth-grade students at SDN 255 Sungai Kapas. This study is a quantitative correlation study. The population of the study was all 66 fourth-grade students. Data collection on learning discipline was conducted using a questionnaire with a Likert scale, while data on Civics learning outcomes were obtained through documentation of final-semester exam scores. Hypothesis testing was conducted using the Pearson Product-Moment correlation test. Research Results: Based on data analysis, a correlation coefficient (rxy) of 0.312 was obtained. The results of the hypothesis test showed that the p-value was <0.05, thus the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The contribution of the learning discipline variable to Civics learning outcomes was 9.7% (Coefficient of Determination), while the remaining 90.3% was influenced by other factors. Based on the hypothesis, Ha indicates a relationship between learning discipline and Civics learning outcomes of fourth-grade students at SDN 255 Sungai Kapas. Therefore, it can be concluded that learning discipline significantly contributes to the achievement of Civics learning outcomes in fourth-grade students at SDN 255 Sungai Kapas in the 2025/2026 academic year.